Ministry as Womb and Tomb: Baptism as a Paradigm for Ministry. (June 2014) - Norheim, Bård Eirik Hallesby
Abstract This article rethinks a paradigm for ministry in a world in which a culture of choice is radically challenging sacramental, baptismal theology. Drawing on the two fundamental biblical metaphors for baptism—baptism as a womb (John 3) and a tomb (Rom 6)—the article tries to reimagine ministry emerging from these two metaphors. The article concludes by emphasizing the importance of developing ministry by the use of this dialectic—ministry as both womb and tomb.